Systemic Lupus Erythematosus in Hemodialysis: Survival Comparison and Mortality-Related Factors - Hwajeong Lee; Seok-Hui Kang (Medicina)
Background and Objectives: We aimed to evaluate the outcome of systemic lupus erythematosus (SLE) patients undergoing hemodialysis (HD) by comparing the survival among HD patients with SLE, diabetes mellitus (DM), or other diseases in the Korean population. We also analyzed the factors affecting the survival of SLE patients undergoing HD. Materials and Methods: This retrospective study analyzed laboratory data from a national HD quality assessment program and claims data. The programs included maintenance HD patients aged ≥18 years. The patients were divided into three groups according to underlying comorbidities as follows: SLE (n = 569), DM (n = 24,665), and others (n = 31,004). Results: The Kaplan–Meier curve showed that the SLE group had better survival than the other two groups. Multivariate analysis showed that the hazard ratios were 0.89 (p = 0.334) in the others group and 1.32 (p = 0.015) in the DM group compared to those in the SLE group. In the SLE group, age, the Charlson Comorbidity Index (CCI) score, hemoglobin, serum creatinine levels, and systolic blood pressure (SBP) were associated with patient survival. Conclusions: This study showed that HD patients with SLE had better patient survival than those with DM and comparable survival with those with other diseases, except SLE or DM. In addition, age, CCI score, hemoglobin, serum creatinine level, and SBP were associated with survival in HD patients with SLE.